The Beginning of Seasonal Herding in Dalmatia (Archaeologia Adriatica, 2022)
Dairying in general, and the production of fermented milk products in particular, are farming strategies that often involve the seasonal movement of herds. Recently published analyses of fatty acid residues on pottery and oxygen isotope analyses of ovicaprine teeth indicate that herders from the northern Dalmatian coast began to move their flocks to summer highland pastures in the second half of the 6th millennium BC, roughly at the same time when they began to make cheese. Results of that research, carried out on archaeological remains from lowland Neolithic villages, are supported and supplemented by the available evidence from highland sites located on Velebit Mountain. Seasonal vertical movement of shepherds began around the middle of the 6th millennium BC, about five centuries after farming first appeared in northern Dalmatia. This change in herd management strategy is roughly contemporaneous with other changes that reflect an intensification of subsistence practices. The spread of farming into the hinterland of Lika may be directly related to the beginning of transhumant  pastoralism.